ANALISIS PENGAPLIKASIAN FOUNDATION MENGGUNAKAN TEKNIK BAKAR TERHADAP KUALITAS HASIL TATA RIAS WAJAH PESTA MALAM PADA KULIT WAJAH BERMINYAK - Laju Annisa Salsabila Yuliardi (Beauty and Beauty Health Education, 2021)
abstract, The development of the world of beauty is one of them in the application of foundations, with various kinds, one of which is the foundation burning technique. Various types of facial skin adjust to the application technique, one of which is oily facial skin, it is difficult to apply makeup because many foundations are less attached to the face, so there needs to be a new technique, namely the burning technique, a technique that is made with a mixture that is burned on wax until blends and then immediately applied to the face of oily skin, so that the foundation is sticky and looks like it closes the pores on the facial skin and looks smooth and durable. Foundation formula varies depending on the type of facial skin, therefore choosing the right foundation must be adjusted to the skin type. Skin types include normal skin, oily skin, and dry skin. Facial skin types that require a long-lasting foundation formulation are oily facial skin types. Oily skin is caused by the oil glands that cannot control the production of oil in the face, causing excess oil production. The aim of the study. To find out the results of applying Foundation using the Burning Technique to the quality of party make-up on oily facial skin, in this there is a validator test by determining the sensory test and preference test in each product. The results of the sensory test were declared feasible with an average of 83.33%, on the favorite test 81.67% were declared the likes of the community. Conclusion The results of applying foundation using the burn technique on party make-up at night, with the sensory test by obtaining an average result of 83.33% which is declared very feasible so that research can be carried out on the community for oily facial skin, and assessed by a preference test various assessment indicators, namely moisture, coverability, smoothness of texture, smoothness of color and durability are criteria for very fond of the percentage of 81.67%, this can be seen that the application of makeup at night party has long lasting quality, and sticks to oily facial skin. . To MUA or facial makeup to be more creative, innovative in utilizing the application of foundation with various types of facial skin in order to produce long lasting results and smooth on the application of makeup.Key words: foundation, burning technique, evening party make-up Abstrak. Formula foundation berbeda-beda tergantung jenis kulit wajah oleh karena itu dalam pemilihan foundation yang tepat harus disesuaikan dengan jenis kulit. Jenis kulit diantaranya adalah kulit normal, kulit berminyak, dan kulit kering. Jenis kulit wajah yang membutuhkan formulasi foundation yang tahan lama adalah jenis kulit wajah berminyak. Kulit berminyak disebabkan oleh kelenjar minyak yang tidak dapat mengontrol produksi minyak di wajah sehingga menyebabkan produksi minyak berlebih. Tujuan penelitian Mengetahui hasil pengaplikasian Foundation menggunakan Teknik Bakar terhadap kualitas hasil tata rias wajah pesta pada kulit wajah berminyak, pada ini adanya uji validator dengan menetapkan uji inderawi dan uji kesukaan dalam setiap produknya. Hasil uji inderawi dinyatakan layak dengan rata-rata 83,33%, pada uji kesukaan 81,67% yang dinyatakn kesukaan pada masyarakat. Simpulan Hasil pengaplikasian foundation dengan menggunaka teknik bakar pada rias wajah pesta malam hari, dengan adanya uji inderawi dengan memperoleh hasil rata-rata 83,33% yang dinyatakan sangat layak sehingga dapat dilakukan penelitian kepada masyarakat untuk kulit wajah berminyak, dan dinilai dengan uji kesukaan dengan berbagai indikator penilaian yaitu kelembaban, daya penutup, kehalusan tekstur, kehalusan warna dan daya tahan merupakan kriteria sangat suka dengan prsentase 81,67%, hal ini terlihat bahwa pengaplikasian fundation rias wajah pesta malam hari memiliki kualitas tahan lama, dan menempel pada kulit wajah berminyak. Kepada MUA atau perias wajah agar dapat lebih kreatif, inovatif dalam memanfaatkan pengaplikasian foundation dengan berbagai jenis kulit wajah supaya menghasilkan hasil yang tahan lama, dan halus pada pengaplikasian rias wajah. Kata kunci: foundation, teknik bakar, tata rias wajah pesta malam